A prospective study of prevalence and characterization of headache following mild traumatic brain injury - Lucas, Sylvia; Hoffman, Jeanne M; Bell, Kathleen R; Dikmen, Sureyya (Cephalalgia, 2014)
Headache is one of the most common and persistent symptoms following traumatic brain injury (TBI). The current study examines the prevalence and characteristics of headache following mild TBI (mTBI). We prospectively enrolled 212 subjects within one week of mTBI who were hospitalized for observation or other system injuries in a single level 1 US trauma center and followed by telephone at three, six, and 12 months after injury for evaluation of headache. Headaches were classified according to ICHD-2 criteria as migraine, probable migraine, tension-type, cervicogenic, or unclassifiable headache. Subjects were 76% male and 75% white, and 58% were injured in vehicle-related crashes. A follow-up rate of 90% (190/212) occurred at 12 months post-injury. Eighteen percent (38/212) of subjects reported having a problem with headaches pre-injury while 54% (114/210) of subjects reported new or worse headaches compared to pre-injury immediately after injury, 62% (126/203) at three months, 69% (139/201) at six months, and 58% (109/189) at one year. Cumulative incidence was 91% (172/189) over one year. Up to 49% of headaches met criteria for migraine and probable migraine, followed by tension-type headaches (up to 40%). Age (≤ 60) was found to be a risk factor, but no significant difference was found in persistence of new or worse headache compared to pre-injury between males and females. More than one-third of the subjects reported persistent headache across all three follow-up time periods. Headache after mTBI is very common and persistent across the first year after injury. Assertive, early treatment may be warranted to avoid chronicity and disability. Further research is needed to determine whether post-traumatic headache (PTH) responds to headache treatment used in the primary headache disorders and whether chronic PTH is preventable.